Leverage and Environmental Cost Disclosure: Evidence from Indonesian Public Companies with Firm Size as Moderator - Dewi Nur Maulidiyah (Fairness, 2026)
Objective: This study examines the effect of leverage on environmental cost disclosure and investigates the moderating role of firm size among Indonesian public companies.Research Design & Methods: This study uses a quantitative approach with panel data collected from 2020 to 2025 on companies that were included in the Kompas100 Index. Purposive sampling was applied, resulting in 130 non-financial companies after excluding financial sector, suspended, and delisted firms. Data were analyzed using panel logit regression.Findings: The results indicate that leverage negatively affects environmental cost disclosure, suggesting that companies with higher debt levels tend to be less likely to disclose environmental costs. Firm size positively affects environmental cost disclosure and weakens the negative effect of leverage on disclosure. This finding indicates that larger firms are more likely to maintain environmental transparency despite higher financial pressure.Implications: The findings imply that financial conditions influence corporate environmental transparency decisions. Companies are encouraged to maintain environmental cost disclosure practices to strengthen legitimacy and stakeholder trust. Regulators are also expected to enhance sustainability reporting standards related to environmental costs.Contribution & Value Added: This study contributes to environmental accounting literature by analyzing environmental cost disclosure using a panel logit regression approach. The study also offers novelty by positioning firm size as a moderating variable in the relationship between leverage and environmental cost disclosure.